2001
DOI: 10.1897/1551-5028(2001)020<1059:ariwm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine Remediation in Wetland Microcosms

Abstract: Laboratory wetland microcosms were used to study treatment of atrazine in irrigation runoff by a field-scale-constructed wetland under controlled conditions. Three experiments, in which 1 ppm atrazine was added to the water column of three wetland, one soil control, and one water control microcosm, were conducted. Atrazine dissipation from the water column and degradate formation (deethylatrazine [DEA]; deisopropylatrazine [DIA]; and hydroxyatrazine [HA]) were monitored. Atrazine dissipation from the water col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
7
0
5
Order By: Relevance
“…In mesocosms planted with rice cutgrass [ Leersia oryzoides (L.) Sw.] and broad‐leaf cattails ( Typha latifolia L.), Moore et al (2017) reported greater atrazine removal (51 ± 6.1% and 53 ± 1.9%, respectively) compared with unvegetated controls (28 ± 17%). Runes et al (2001) noted wetland microcosms, via sorption and degradation, were able to reduce atrazine concentrations in the water column. Runes et al (2003) also reported constructed wetlands were able to mitigate 16 to 24% of atrazine associated with nursery irrigation runoff.…”
Section: Resultsmentioning
confidence: 99%
“…In mesocosms planted with rice cutgrass [ Leersia oryzoides (L.) Sw.] and broad‐leaf cattails ( Typha latifolia L.), Moore et al (2017) reported greater atrazine removal (51 ± 6.1% and 53 ± 1.9%, respectively) compared with unvegetated controls (28 ± 17%). Runes et al (2001) noted wetland microcosms, via sorption and degradation, were able to reduce atrazine concentrations in the water column. Runes et al (2003) also reported constructed wetlands were able to mitigate 16 to 24% of atrazine associated with nursery irrigation runoff.…”
Section: Resultsmentioning
confidence: 99%
“…Common measurements of contaminant fate include partitioning from the water column into sediments, macrophytes, and particulate and dissolved organic material. Although these studies (Ronday et al 1997;Runes et al 2001;Bouldin et al 2004b) provide practical suggestions for BMPs to manage runoff and address water-quality criteria concerns, the array of likely pesticide degradation products is ill defined and costly to measure.…”
Section: Discussionmentioning
confidence: 99%
“…Attributes of these systems that modify runoff include vegetative and sediment interactions, residence time, and spatial distance from point of input (Bouldin et al 2004a). Macrophyte communities act as a sink for runoffassociated pesticides and also increase hydraulic retention time in agricultural receiving systems (Runes et al 2001;Schulz et al 2003). The importance of retention time has been noted for the uptake rates of various pesticides (Lytle & Lytle 2002) and has been illustrated in studies addressing vegetated agricultural drainage ditches and constructed wetland cells (Bouldin et al 2004a(Bouldin et al , 2004bMilam et al 2004).…”
mentioning
confidence: 99%
“…In water-sediment systems treated with [ 14 C]atrazine, Mersie et al [29] observed that increased retention of 14 C by sediment coincided with greater detection of HYA. Runes et al [30] reported that HYA was the predominant degradate in the sediment of laboratory wetland microcosm. In this study, sediments were extracted three times with aqueous methanol.…”
Section: Atrazinementioning
confidence: 99%
“…Researchers have reported more rapid hydrolysis of atrazine to hydroxyatrazine in sterilized soil compared to soil-free systems, which suggests that soil catalyzed hydrolysis reactions [34]. Hydroxyatrazine can be formed as a result of photolytic hydrolysis or chemical or biological degradation [21][22][23]; has been found to be a predominant degradate in sediment [30]; is more readily adsorbed to wetland soils and aquifer solids than atrazine [27,28]; and has a greater sorption coefficient than ATR, DIA, or DEA [26][27][28], which suggests the sediment-bound residues would primarily consist of HYA. This is further implied by the results of Lerch et al [31], who reported exhaustive mixed-mode extraction of soil-bound residues from aqueous methanol-extracted atrazine-treated soil, recovered substantial quantities of HYA.…”
Section: Co 2 Was Insignificant (յ01%)mentioning
confidence: 99%